2003
DOI: 10.1590/s0066-782x2003000900001
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with Mycoplasma Pneumoniae and Chlamydia Pneumoniae in ruptured plaques associated with acute myocardial infarction

Abstract: OBJECTIVE: To study atheromas, Mycoplasma pneumoniae (M. pneumoniae), and Chlamydia pneumoniae (C. pneumoniae). METHODS: C. pneumoniae was studied with immunohistochemistry and M. pneumoniae with in situ hybridization (ISH), in segments of coronary arteries (SCA) as follows: group A - thrombosed ruptured plaques (TRP) of 23 patients who died due to acute myocardial infarction (AMI); group B - 23 nonruptured plaques (NRP) of group A patients; group C - NRP of 11 coronary patients who did not die due to AMI; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
(61 reference statements)
3
30
0
9
Order By: Relevance
“…We have previously reported that Chlamydia pneumoniae and Mycoplasma pneumoniae are present in atherosclerotic plaques 15,17,18 . Given the similarity between atherosclerosis and aortic valve stenosis, we hypothesized that such agents may also be present in AS and play an important role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have previously reported that Chlamydia pneumoniae and Mycoplasma pneumoniae are present in atherosclerotic plaques 15,17,18 . Given the similarity between atherosclerosis and aortic valve stenosis, we hypothesized that such agents may also be present in AS and play an important role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Chlamydia pneumoniae (CP) has been suggested to be involved in the pathogenesis of atherosclerosis, related with gene polymorphisms 14 and inflammation 15 but this still is a controversial matter [16][17][18] . CP has also been associated with the inflammatory processes of aortic valve lesions 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inability of the host organism to completely eliminate the pathogen leads to a chronic infection state, which can cause tissue damage sequelae. Thus, the infection, dissemination and development of immunity against Chlamydophila pneumoniae seem to have an important role in several diseases such as reactive arthritis, atherosclerosis, Alzheimer disease, and multiple sclerosis (28,29). A possible role of coinfection by M. pneumoniae and C. pneumoniae has been associated with the progress of atherosclerosis (29).…”
Section: Is Lyme Disease-like Syndrome a New Tick-borne Disease?mentioning
confidence: 99%
“…Thus, the infection, dissemination and development of immunity against Chlamydophila pneumoniae seem to have an important role in several diseases such as reactive arthritis, atherosclerosis, Alzheimer disease, and multiple sclerosis (28,29). A possible role of coinfection by M. pneumoniae and C. pneumoniae has been associated with the progress of atherosclerosis (29). Mycoplasma induces immunological changes in the host defenses that favor growth of other microorganisms (30).…”
Section: Is Lyme Disease-like Syndrome a New Tick-borne Disease?mentioning
confidence: 99%